Mastering integrated HTML and CSS - DeBolt, Virginia (Wiley Pub., 2007)
This unique approach to learning HTML and CSS simultaneously shows you how to save time and be more productive by learning to structure your (X) HTML content for best effect with CSS styles. You’ll discover how to create websites that are accessible to the widest range of visitors, build CSS for print and handheld devices, and work with a variety of CSS-based layouts. Using the latest standards, best practices, and real-world examples, this book offers you with a thorough grounding in the basics and also includes advanced techniques.